Analysis of microvasculature phenotype and endothelial activation markers in skin lesions of lacaziosis (Lobomycosis). (January 2015) - Quaresma, Juarez A.S.; Brito, Maysa V.; Sousa, Jorge R.; Silva, Luciana M.; Hirai, Kelly E.; Araujo, Rafael S.; de Brito, Arival C.; Carneiro, Francisca R.O.; Fuzii, Hellen T.; Pagliari, Carla; Sotto, Mirian N.; Duarte, Maria I.S.
Abstract: Jorge Lobo's disease is a rare mycosis characterized by chronic inflammation, which causes skin lesions in the absence of visceral dissemination. The disease occurs mainly in hot and humid climates and most cases have been registered in the Brazilian Amazon region. This study investigated possible microvascular alterations in skin lesions caused by infection with Lacazia loboi which may interfere with the clinical progression of the disease. Immunohistochemistry was used to evaluate the density of blood and lymphatic vessels, as well as expression of the cell adhesion molecules ICAM-1, VCAM-1 and E-selectin. The results showed a reduced number of blood (62.66 ± 20.30 vessels/mm 2 ) and lymphatic vessels (3.55 ± 5.84 vessels/mm 2 ) in Jorge Lobo's disease when compared to control skin (169.66 ± 66.38 blood vessels/mm 2 and 8 ± 2.17 lymphatic vessels/mm 2 ). There were a larger number of vessels expressing ICAM-1 (27.58 ± 15.32 vessels/mm 2 ) and VCAM-1 (7.55 ± 6.2 vessels/mm 2 ). No difference was observed in the expression of E-selectin (4.66 ± 11 vessels/mm 2 ). Taken together, the results indicate changes in the local microvasculature which may interfere with the development of an efficient cell-mediated immune response and may explain restriction of the fungus to the site of injury. Highlights: Jorge Lobo's disease is a rare mycosis characterized by chronic inflammation. Immunohistochemistry was used to evaluate the density of blood and lymphatic vessels in lesions. Results indicate changes in the local microvasculature. These alterations may interfere cell-mediated immune response.